U.K. World War I and interwar data for business cycle and growth analysis - James Michael Nason; Shaun P. Vahey (Federal Reserve Bank of Atlanta, 2009)
This article contributes new time series for studying the U.K. economy during World War I and the interwar period. The time series are per capita hours worked and average tax rates of capital income, labor income, and consumption. Uninterrupted time series of these variables are provided for an annual sample that runs from 1913 to 1938. We highlight the usefulness of these time series with several empirical applications. We use per capita hours worked in a growth accounting exercise to measure the contributions of capital, labor, and productivity to output growth. The average tax rates are employed in a Bayesian model averaging experiment to reevaluate the Benjamin and Kochin (1979) regression.
Keywords: E32; E62; N14; N34; N44; 330; hours worked; average tax rates; growth accounting; Bayesian model averaging; Wirtschaftswachstum; Zeitreihenanalyse; Schätzung; Großbritannien